Imagem, corpo e axé: fabulações críticas da afrorreligiosidade em videoclipes de artistas negros(as) brasileiros contemporâneos(as) - Barbosa, Anna Victória da Silva Paes (2026)
This research aims to understand how the incorporation of elements of afro-religiosity in music videos by black brazilian artists contributes to the construction of critical fabulations (Hartman, 2020), which update archives of images of black experiences and their artistic and cultural practices. By identifying and historicizing the presence of this theme in brazilian music, the study seeks to highlight the creation of counter-historical narratives in audiovisual productions. Part of the pillars of music and media studies (Cardoso Filho, 2006; Janotti Jr., 2006; Soares, 2014), performance studies (Martins, 2021; Taylor, 2013), race relations studies (Bento, 2022; Sodré, 2023) and critical archival studies (Hartman, 2020; Foucault, 1969; Taylor, 2013). The approach to communication and consumption adopted here is anchored in the perspective of mass popular music studies, understanding music videos as media products inserted in a dynamic chain of production, reception, and circulation of music in media contexts. Through the methodological appropriation of the filmic constellation (Souto, 2020), adapted to the materiality of the music video, we seek to categorize the complex diversity of contemporary afro-brazilian expressions. As a methodological process, the research adopts an exploratory approach, based on the survey and preliminary analysis of more than 30 music videos by black brazilian artists. This mapping allowed us to identify aesthetic, performative, and narrative recurrences (such as the centrality of the body, the mobilization of Orixás, and the predominant musical genres), guiding the constitution of the final corpus, composed of four music videos analyzed in depth: Tranca Rua (ÀTTØØXXÁ and Baco Exu do Blues), Reza Forte (BaianaSystem feat. BNegão), coração tambor (fran), and Pra que me chamas? (Xênia França). The definition of the corpus was part of the analytical process itself, highlighting patterns that run through contemporary audiovisual productions. Anchored in a critical perspective of archives, the research mobilizes critical fabulation to understand the music video as a living archive, in which memory, performance, and invention challenge the silences of official history and produce counter-historical narratives in the realm of mass popular music.